Evaluation of Motility, Viability, and Integrity Plasma Membranes of Frozen Semen in Friesian Holstein with Storage Periods of 33, 30, 27, and 24 Years - Purnawan, Ahmad Budi; Rimayanti, Rimayanti; Susilowati, Suherni; Mustofa, Imam; Hernawati, Tatik; Safitri, Erma (Jurnal Medik Veteriner, 2023)
The quality of frozen semen is one of the components of the artificial insemination program. The freezing method, kind of diluent, handling of frozen semen, and thawing process all affect the quality of frozen semen. This study aimed to determine the motility, viability, and plasma membrane integrity of frozen semen of Friesian Holstein cattle at storage periods of 33, 30, 27, and 24 years. The samples used were stored for 33 years (production 1987), 30 years (production 1990), 27 (1993 production), and 24 years (1996 production) stored in Singosari Artificial Insemination Center, Malang. Data were statistically analyzed using One-Way ANOVA followed by Duncan's Multiple Range Test (p < 0,05). Based on the study's findings, it can be concluded that the motility, viability, and plasma membrane integrity of frozen semen that had been preserved for 33, 30, 27, and 24 years were still acceptable and in good condition in comparison to the SNI quality criteria for bull frozen semen in Indonesia.